Zhenshchiny v iznachal'no muzhskikh vidakh sporta - Gasanova, Z. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this paper was to discuss the problem of women participation in sports, which were created for man from the beginning of their history. The author shows that the contemporary sports achievements of women are much more significant than at the beginning of their participation in these sports (the difference between them decreased now from 20 to 10%, approximately.